Judge's Reasoning Against the Dispensation of Marriage of Minors Due to Pregnancy After the Enactment of Law No. 16 of 2019 (Study of the Pandan Religious Court) - Emma Andini; Muhammad Yadi Harahap (Warmadewa Press, 2024)
Marriage Dispensation from the Court is a decision in the form of determining a dispensation for prospective male or female brides who have law number 16 of 2019 states that you must not have married before you turn 19 years old. Even if there is a legislation that restricts the minimum age at which one can be married, refer to this potential anomaly as underage marriage. Consequently, if a man and a woman get married before turning 19, it's referred to as underage marriage. The research methodology employed is normative juridical, which involves examining theoretical frameworks, concepts, pertinent statutory rules, and legislative procedures. Judges of the Pandan Religious Court were directly interviewed as part of the data collection process. According to research, the judge will allow the request for marriage dispensation under the legal rationale. Marriage dispensation is the term used to describe when a court permits a prospective husband and wife who are under the age of 19 to get married. To aid in the effective administration of justice, the Chief Justice of the Republic of Indonesia established Regulation of the Supreme Court of the Republic of Indonesia Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation. Marriage dispensation applications are not clearly and thoroughly governed by statute. This regulation was drafted on November 20, 2019, and it was formally published on November 21 to ensure that everyone in society may read it and abide by it.